Prostate specific membrane antigen positron emission tomography for lesion-directed high-dose-rate brachytherapy dose escalation. (July 2021) - Smith, Christopher W.; Alfano, Ryan; Hoover, Douglas; Surry, Kathleen; D'Souza, David; Thiessen, Jonathan; Rachinsky, Irina; Butler, John; Gomez, Jose A.; Gaed, Mena; Moussa, Madeleine; Chin, Joseph; et al.
Highlights: This paper evaluated lesion-directed prostatic high dose rate brachytherapy. Lesions defined by prostate specific membrane antigen positron emission tomography. Dose escalation was confirmed using whole-mount digital histology. Targeting lesions led to significantly higher dose to high-grade histologic cancer. Abstract: Background and purpose: Prostate specific membrane antigen positron emission tomography imaging (PSMA-PET) has demonstrated potential for intra-prostatic lesion localization. We leveraged our existing database of co-registered PSMA-PET imaging with cross sectional digitized pathology to model dose coverage of histologically-defined prostate cancer when tailoring brachytherapy dose escalation based on PSMA-PET imaging. Materials and methods: Using a previously-developed automated approach, we created segmentation volumes delineating underlying dominant intraprostatic lesions for ten men with co-registered pathology-imaging datasets. To simulate realistic high-dose-rate brachytherapy (HDR-BT) treatments, we registered the PSMA-PET-defined segmentation volumes and underlying cancer to 3D trans-rectal ultrasound images of HDR-BT cases where 15 Gray (Gy) was delivered. We applied dose/volume optimization to focally target the dominant intraprostatic lesion identified on PSMA-PET. We then compared histopathology dose for all high-grade cancer within whole-gland treatment plans versus PSMA-PET-targeted plans. Histopathology dose was analyzed for all clinically significant cancer with a Gleason score of 7or greater. Results: The standard whole-gland plans achieved a median [interquartile range] D98 of 15.2 [13.8–16.4] Gy to the histologically-defined cancer, while the targeted plans achieved a significantly higher D98 of 16.5 [15.0–19.0] Gy (p = 0.007). Conclusion: This study is the first to use digital histology to confirm the effectiveness of PSMA-PET HDR-BT dose escalation using automatically generated contours. Based on the findings of this study, PSMA-PET lesion dose escalation can lead to increased dose to the ground truth histologically defined cancer.